Novel ytterbium Schiff base complex: Toward efficient solution-processed NIR-emitting OLED - Kornikov, Andrey I.; Mustakimov, Robert E.; Goloveshkin, Alexander S.; Tcelykh, Lyubov O.; Vashchenko, Andrey A.; Medvedko, Aleksei V.; Lepnev, Leonid S.; Utochnikova, Valentina V. (Organic electronics, 2022)
Lanthanide complexes Ln(L)(HL) (H2L = 2-tosylamino-benzylidene-(2-benzo[d]thiazole) hydrazone; Ln = Yb, Gd) were obtained and thoroughly characterized. The monomeric structure of Yb(L)(HL)·Solv1 (Solv1 = 2CH3CN + 2EtOH + H2O) and the ligand structure were determined by single crystal X-ray diffraction data. Relatively high solubility (ca. 5 g/l) and quantum yield (0,9%), as well as mobility of electrons (2,33·10−6 cm2/V·s) and holes (4,94·10−7 cm2/V·s) of Yb(L)(HL) allowed its successful use as a host-free near-infrared OLED emission layer. OLED with the heterostructure ITO/PEDOT:PSS/poly-TPD/Yb(L)(HL)/OXD-7/LiF/Al demonstrated pure 1000 nm centred near-infrared luminescence with the external quantum efficiency up to 0.025%, which is one of the highest value for 1000 nm centred electroluminescence. [Display omitted] •Ytterbium coordination compound Yb(L)(HL)·Solv with 2-tosylamino-benzylidene-(2-benzo[d]thiazole) hydrazone was obtained.•Crystal structures of the complex and the new ligand were determined.•Yb(L)(HL)·Solv demonstrate ytterbium luminescence with the quantum yield up to 0,9% and high solubility.•Mobility of charge carriers was measured (2,33·10−6 cm2/V·s and 4,94·10−7 cm2/V·s for electrons and holes).•Yb(L)(HL)·-based solution-processed host-free OLED demonstrated the pure 1000 nm centred NIR emission at low voltages.